Survey of Basic Bolavoli Skills In Extracurricular Students At SMP Negeri 4 Kaur District - Fikri, Muhammad; Elra Perdima, Feby; sumantri, Ajis (Sinar Sport Journal, 2023)
The purpose of this study was to determine the level of basic skills of volleyball games in extracurricular students at SMP Negeri 4 Kaur Regency. The method used in this research is a survey research method using a quantitative descriptive approach. Data collection techniques using test data, secondary data and measurement scales. Data analysis was carried out descriptively quantitatively with a percentage using the survey method. The results showed that the basic technical skills of extracurricular bolavoli students at SMP Negeri 4 Kaur Regency as a whole were in the good enough category or 66%.